2016
DOI: 10.21505/ajge.2016.0012
|View full text |Cite
|
Sign up to set email alerts
|

Parents' experiences with their children's grade-based acceleration: Struggles, successes, and subsequent needs

Abstract: Grade-based acceleration is when high-ability children progress through school at a rate faster than typical by being placed with older classmates. This educational practice can help meet the learning needs of high-ability children. In this study, 56 parents of high-ability children who underwent grade-based acceleration in Australian schools shared their experiences through an online questionnaire. We posed the following research question: "What are the experiences of parents whose children accelerate into cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Hesitation to implement accelerative practices is often linked to concerns about socioemotional outcomes and social acceptance (Dare et al, 2016; Gallagher & Smith, 2013; Gross et al, 2011; Rambo & McCoach, 2012; Siegle et al, 2013). Some participants in this study shared similar concerns about grade-based acceleration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hesitation to implement accelerative practices is often linked to concerns about socioemotional outcomes and social acceptance (Dare et al, 2016; Gallagher & Smith, 2013; Gross et al, 2011; Rambo & McCoach, 2012; Siegle et al, 2013). Some participants in this study shared similar concerns about grade-based acceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Decision makers must consider a complex interplay of factors when deciding whether acceleration is an appropriate intervention for an individual student. Research shows that acceleration most often results in both positive academic and social outcomes (Assouline et al, 2015; Dare et al, 2016; Hattie, 2009; Steenbergen-Hu et al, 2016; Steenbergen-Hu & Moon, 2011). Although quantitative research suggests that social challenges are the exception (Steenbergen-Hu & Moon, 2011), some individuals have perceived challenging socioemotional consequences following whole-grade acceleration (Neihart, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grade-based acceleration is also known as grade skipping, and it is often thought as the only form of acceleration (Dare, Smith, & Nowicki, 2016). However, within the classification mentioned above, different authors (Southern & Jones, 2004Southern, Jones, & Stanley, 1993) have presented types of acceleration showing at least 18 different options.…”
Section: A) Accelerated Learningmentioning
confidence: 99%
“…Also, parents' experiences about acceleration are also critical. Dare et al (2016) concluded that parents perceive positive academic, emotional and social outcomes from acceleration.…”
Section: A) Accelerated Learningmentioning
confidence: 99%